Analisis Kesesuaian Prinsip Syariah Pada Akad Dan Standar Operasional Prosedur (Sop) Pembiayaan Di Baitul Maal Wa Tamwil Islam Abdurab Pekanbaru - Madona Khairunisa; Nur Hasanah; Mohd Winario (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to analyze the compliance of contracts and the Standard Operating Procedures (SOP) of financing at Baitul Maal wat Tamwil Islam Abdurrab (BMTIA) Pekanbaru with sharia principles. As a sharia-based microfinance institution, BMTIA plays an important role in providing financing that aligns with Islamic values, such as the prohibition of riba (usury), gharar (uncertainty), maysir (gambling), and the application of justice principles. This research employs a qualitative approach through the analysis of SOP documents. The results show that most of the financing procedures implemented by BMTIA are in accordance with sharia principles, particularly in terms of contract selection, financing mechanisms, and supervisory systems. However, there are several aspects that still need improvement, such as transparency of information to customers and monitoring of financing implementation. Therefore, this study recommends refining the SOP to ensure better alignment with sharia principles and to enhance public trust. These findings are expected to contribute to the development and supervision of Islamic microfinance institutions in IndonesiaKeywords: SOP, Financing, Sharia Principles, BMT, Usury, Sharia MicrofinanceArticle history: